STUDY OF THE INCIDENCE AND PREVALENCE OF EPILEPSY IN MINSK - T. V. Dokukina; T. S. Golubeva; I. V. Matveichuk; M. V. Mahrov; V. M. Loseva; E. V. Krupenkina; S. A. Marchuk (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: epidemiological study of epilepsywas carried out in Minsk. Aim: study of the incidence and prevalence of epilepsy in the gender-age population groups in Minsk. Materials and Methods: A retrospective study was carried out by assessing the medical data of the outpatient case report forms of patients with epilepsy who were seeking medical aid during the period 2008-2012. Results: Overall incidence of epilepsy ranged from 165.2 per 100,000 population in 2008 to 275.5 per 100,000 population in 2012; incidence of primary epilepsy ranged from 36.9 per 100,000 population in 2008 to 25.0 per 100,000 population in 2012. The prevalence of epilepsy was 6.06 per 1000 population. Etiological factors that increase the risk of developing epilepsy were head injuries (28.6%), neuroinfection (13.3%), chronic alcoholism (10.0%), vascular diseases of the brain (6.7%), perinatal pathology (5 , 2%), brain tumor (2.9%). In 33.3% of patients the cause of the disease has not been established. Conclusions: the prevalence of epilepsy in Minsk is comparable with the prevalence level in the European developed countries. It seems appropriate to create a unified electronic database of patients with epilepsy and continue studies targeted on finding ways for solving medical and social problems in the Republic of Belarus.